Efficacy of low dose intravenous dexmedetomidine versus clonidine in treatment of shivering during caesarean section under spinal anaesthesia: a double blind randomized controlled trial - Karamchand Basumatary; Diganta Saikia; Ratindra Kumar Barman; Jagadish Basumatary; Joyanta Kumar Choudhury; Shashankar Das (Barpeta Obstetrics and Gynaecological Society, 2023)
Objectives: Dexmedetomidine and clonidine have been used to prevent and treat shivering after spinal anaesthesia. A double blind randomized controlled trial was conducted to compare the efficacy and safety of low dose intravenous dexmedetomidine and clonidine in controlling post-spinal anaesthesia shivering during caesarean section. Methods: 260 pregnant women of American Society of Anesthesiologists physical status I and II, aged between 18 - 40 years posted for caesarean section who developed grade 3 or 4 shivering after spinal anaesthesia were randomly divided into two groups, Group D (n = 130) received intravenous dexmedetomidine 0.5 μg/kg and Group C (n = 130) received clonidine 0.5 μg/kg. Time required to control shivering, response rate, recurrence rate, and adverse effects were observed. Results: The time taken to cease the shivering was short (2.20 ± 0.35 min) with no recurrence in dexmedetomidine in comparison with clonidine group (5.51 ± 0.48 min). There was 27.69% recurrence with clonidine. Response rate was 100% in dexmedetomidine against 82.3% of clonidine group. The sedation level was adequate with dexmedetomidine without respiratory depression. The haemodynamic parameters and other side effects were comparable and no adverse neonatal outcome was observed in both the groups. Conclusion: Intravenous dexmedetomidine 0.5 μg/kg has early onset of effect, higher response rate without recurrence with added advantage of good sedation and stable cardiorespiratory function and neonatal outcome than clonidine 0.5 μg/kg in controlling post-spinal anaesthesia shivering during caesarean section.